The effects of IPad applications on creative thinking and learning motivation among preschool children in Jordan - Al-Zu'bi, Mohammad Ahmad Abdelaziz (2019)
IPad applications have positive evidences to promote literacy and academic outcomes among preschool children, but iPad applications contributing to creative thinking and learning motivation are still scarce in Jordan. Thus, this study will help to develop a new curriculum for preschool as part of Jordanian Education reforms. The present research aims to investigate the effects of iPad applications on creative thinking and learning motivation among Jordanian preschool children. The research used a quasi-experimental non-equivalent group design involving 67 children (34 girls and 33 boys) at preschool stage (KG2). The experimental group underwent an iPad applications intervention for twelve sessions (30 minutes each) in a regular classroom setting by a trained teacher. Whereas, the control group used traditional curriculum for the same amount of time in a regular classroom setting. Data were gathered for pre-testing and post-testing using TCAM and MLCT-Scale for the variables (creative thinking and learning motivation). The pilot study confirmed the reliability of the questionnaire. A one-way ANCOVA in the post-test revealed that the experimental group have better significant results compared to the control group in relation to all variables. The significant mean differences were observed between the pre-test and post-test for the experimental group with the main effects observed for creative thinking as a result of TCAM-test, and between the means of the pre-test and post-test for the experimental group with the main effects observed for learning motivation as a result of MLCT-Scale. The findings have supported the use of iPad applications in education which could increase the levels of creative thinking and learning motivation. This study recommends that in order to enhance creative thinking and learning motivation among preschool children, iPad applications need to be updated regularly and conducted consistently.